Mental Health Of Lecturers Amid Banditry In Zamfara State: Implications For Counseling And Psychotherapy - Haruna, Abubakar Sadiq; Mayanchi, Mohammed Lawal (Academic Journal of Psychology and Counseling, 2024)
In the context of ongoing banditry incidents in Zamfara State, Nigeria, this study aimed to assess the mental health status of lecturers in Federal University Gusau (FUGUS). The purpose was to examine whether banditry had affected psychological well-being of the university teachers. Employing a descriptive survey design, data were collected from 86 lecturers using a Self-Reporting Mental Health Inventory (SMHI). The inventory demonstrated high internal consistency (Cronbach's alpha = 0.89) and comprised dimensions reflecting positive mental health attributes. Data analysis involved the use of mean scores, one-sample and Independent Sample T-Tests. The results of the analyses revealed that the mean scores for various dimensions of mental health were consistently below 3.0, suggesting a significant level of negative mental health experienced by the participants. Furthermore, an Independent Sample T-Test indicated that gender did not exert a significant influence on the observed negative mental health outcomes (t=-0.195, p>0.05). The findings underscore the need for targeted counselling interventions and support strategies to address negative mental health outcomes among lecturers, irrespective of gender, and to cultivate a conducive academic environment that promotes their psychological well-being.